Autism, Gender and Performativity: Masked Alterities - Briones Marrero, Amanda (Estudios LGBTIQ+, Comunicación y Cultura, 2022)
The purpose of this article is to highlight the problem of gender in autism spectrum disorders and to open the possibility of considering autism from the perspective of the theory of performativity. To do so, it first discusses the reasons why autism has been mainly associated with male sex-gender, and points to studies showing that women, trans, non-binary and agender individuals have been systematically under-diagnosed. This is due to the fact that the traits described for individuals on the spectrum are those displayed by the normative male subject in Leo Kanner and Hans Asperger’s classic studies, and have left out other manifestations of those who have not been socialized as such a subject. Secondly, it argues for the need to apply the theory of performativity to autism spectrum disorders, as this may shed light on the intuition that there is no purely male or female autism, but that autism, like gender itself, is not binary. Finally, it presents a series of final considerations that reinforce the arguments defended throughout the article, and that advocate the need to create a framework of inclusive features and to introduce interdisciplinarity in the field of autism, insofar as this condition does not or should not concern only psychology, biology and medicine, but also social sciences and the humanities.
Keywords: autism; spectrum; gender; performativity; queer